Disharmony of Sirri Marriage Registration Regulation on the Family Card (Analyzing The Ministry of Interior Affairs’ Regulation No. 9/2016) - Lathifah Munawaroh; Ahmad Munif; Ahmad Rofiq (Universitas Lampung, 2023)
The Regulation of the Minister of Interior Affairs of the Republic of Indonesia No. 9 of 2016 concerning the Acceleration of Coverage of Birth Certificate Ownership, in article 4 numbers 2 and 3, allows birth certificate applicants who cannot meet the requirements in the form of a marriage certificate, to get a solution still recorded in the family card by attaching the statement of absolute responsibility, called SPTJM, truth as husband and wife with the editorial status written in the family card